Phytochemical analysis, antioxidant and antimicrobial effects of extracts from grape (Vitis vinifera) by-products and mandarin orange (Citrus reticulata Blanco) - Pfukwa, Trust Mukudzei (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScFoodSc)--Stellenbosch University, 2018.